Napo 2006 - European Agency for Safety and Health at Work.; Allgemeine Unfallversicherungsanstalt; Health & Safety Executive; Hessischen Verwaltung für Bodenmanagement und Geoinformation; Istituto Nazionale Assicurazione contro gli Infortuni sul Lavoro; Institut National de Recherche et de Securite; SuvaPro ([χ.τ.]: [European Agency for Safety and Health at Work], 2007)
Περιέχει 6 ταινίες μικρού μήκους.
Keywords: DVD-ROMs.; Εργατικά ατυχήματα -- Πρόληψη.; Εργασία -- Ασφάλεια.; Εργασία -- Ασφάλεια -- Πρόληψη.